IUEE
EU
Sign in
Ask The Question
English
French
Spanish
Portuguese
Polish
Romanian
Mathematics
Freshkid
Mar 7, 2019, 10:49:40 AM
55
which of the following is equivalent to the equation 2(x-3) 5(x+1)
+5
(
1
) Answers
giuseppag1982
Mar 7, 2019, 11:11:40 AM
(2x-6)(5x+5) 10x^2-20x-30=f(x)
Add answer
Sign in
Sign up
Related Questions
which of the following is equivalent to the equation 2(x-3) 5(x+1)
Which of the following systems is equivalent to the given system? 2/3 x - y = 2 x + 1/2y = -3
Which of the following systems is equivalent to the given system? x - y = 2 x + y = -3
Which of the following equations is equivalent to x - y = 5?
Which of the following expressions is equivalent to the expression x - (-3) ? x - 3 x + (-3) ...
Below are the steps to solve an equation: Step 1: |x − 5| + 2 = 5 Step 2: |x − 5| = 5 − 2 S...
1/2 x + 1/3 y = 3 Which of the following equations is equivalent to the given equation? A) ...
Which equation is equivalent to (1/3)^x = 27 ^x + 2
Remmi wrote the equation of the line y=1/3(x+2) He solved for x and got x=3y-2 Which of the follo...
below are the steps to solve and equation step 1: | x-5 | + 2 = 5 step 2: | x-5 | = 5 - 2 step ...